The institutional matrix of „soft power” policy of the USA - Коротков, Д. С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
The article is devoted to the study of formation and institutionalization of the concept of „soft power" of the United States in the context of their foreign policy. It was determined a significant impact of democratic political values, cultural sphere and free information flow of the United States on the world geopolitical process. It was proved that the systemic actions of all American instruments is the key to the effective use of the policy of "soft power» of the United States.